Investigation Supplement. “Between you and me: no intermediaries” (Interior vestibule) (Praxis Educativa, 2026)
This paper proposes a critical reinterpretation of the origins of the Argentine public school system, focusing on acomponent that dominant historiography has rendered invisible: the influence of the “Protestant path” and thearrival of American teachers, summoned by Domingo F. Sarmiento in the 19th century, to reorganize theeducational system. The central hypothesis is that the public school system was not born as an instrument ofstate discipline, but rather as an experiment in cooperation, popular sovereignty, democracy, secularism,republicanism, and feminist prefiguration. Heirs to the Protestant Reformation, the thought of Comenius, and theEnglish Revolution, it transcended the liberal, Catholic, and cultural frameworks of a nascent state that, bothimmediately and subsequently, sought to discipline it. Methodologically, the paper combines global history,microhistory, and critical genealogy, concluding that the invisibility of the Protestant path constituted an activeoperation of symbolic closure, and its dismantling contributes to the historiographical redress of this initialmeaning
Keywords: Global Classroom/Global Capital; historiographical disputes and Silences in State Building; Genealogies of the Educational System,; Secular, Feminine, State and Republican Pedagogy